2016
DOI: 10.1093/brain/aww017
|View full text |Cite
|
Sign up to set email alerts
|

Early and protective microglial activation in Alzheimer’s disease: a prospective study using18F-DPA-714 PET imaging

Abstract: While emerging evidence suggests that neuroinflammation plays a crucial role in Alzheimer's disease, the impact of the microglia response in Alzheimer's disease remains a matter of debate. We aimed to study microglial activation in early Alzheimer's disease and its impact on clinical progression using a second-generation 18-kDa translocator protein positron emission tomography radiotracer together with amyloid imaging using Pittsburgh compound B positron emission tomography. We enrolled 96 subjects, 64 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
337
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 391 publications
(373 citation statements)
references
References 39 publications
33
337
2
1
Order By: Relevance
“…By using tracers that specifically bind to the translocator protein TSPO -expressed by microglia -it was suggested that microglial activation in AD brain could track temporally and spatially with the spread of amyloid as well as tau [ 5 4 4 _ T D $ D I F F ] pathology [32,33]. Interestingly, higher binding of TSPO ligand has been documented in AD patients with a slower rate of disease progression, raising the possibility that microglial activation can exert a protective effect [34]. Microglia play [ 5 4 5 _ T D $ D I F F ] a myriad of functions in the healthy and diseased brain; however, emerging data from the field suggests that microglia become impaired during neurodegenerative disorders.…”
Section: Trem2: Presenting Microglia Front and Center In Admentioning
confidence: 99%
“…By using tracers that specifically bind to the translocator protein TSPO -expressed by microglia -it was suggested that microglial activation in AD brain could track temporally and spatially with the spread of amyloid as well as tau [ 5 4 4 _ T D $ D I F F ] pathology [32,33]. Interestingly, higher binding of TSPO ligand has been documented in AD patients with a slower rate of disease progression, raising the possibility that microglial activation can exert a protective effect [34]. Microglia play [ 5 4 5 _ T D $ D I F F ] a myriad of functions in the healthy and diseased brain; however, emerging data from the field suggests that microglia become impaired during neurodegenerative disorders.…”
Section: Trem2: Presenting Microglia Front and Center In Admentioning
confidence: 99%
“…A large number of second generation tracers with higher specificity has been developed but their binding is subject to a genetic polymorphisms that blurs the advantage of these tracers [454]. Nonetheless, beyond these limitations, the development of these tracers could provide relevant biomarkers and offer new insights in the variability of evolution of AD [455]. There are also tracers for imaging of astrogliosis, and markers for cytokines and inflammatory endothelial changes are being developed.…”
Section: Contribution and Role Of Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…In another study measuring 11 C-( R )-PK-11195 binding, Okello and colleagues found that only 5 of 13 MCI patients had elevated 11 C-( R )PK-11195 binding and that this was not related to amyloid binding (Okello et al, 2009). Hamelin and colleagues found that amyloid-positive MCI patients had greater 18 F-DPA-714 binding than controls (Hamelin et al, 2016). However, in contrast to the findings of Kreisl et al (2013) and Lyoo et al (2015)—where AD patients had greater TSPO binding than MCI patients—and those of Yasuno and colleagues, which found that MCI and AD patients both had increased binding compared to controls, Hamelin and colleagues found that binding was greater in MCI than in AD patients (Hamelin et al, 2016); that study further found that 18 F-DPA-714 binding was inversely correlated with cognitive measures, with more affected patients having lower TSPO binding.…”
Section: Neuroinflammation In Alzheimer’s Diseasementioning
confidence: 99%
“…Hamelin and colleagues found that amyloid-positive MCI patients had greater 18 F-DPA-714 binding than controls (Hamelin et al, 2016). However, in contrast to the findings of Kreisl et al (2013) and Lyoo et al (2015)—where AD patients had greater TSPO binding than MCI patients—and those of Yasuno and colleagues, which found that MCI and AD patients both had increased binding compared to controls, Hamelin and colleagues found that binding was greater in MCI than in AD patients (Hamelin et al, 2016); that study further found that 18 F-DPA-714 binding was inversely correlated with cognitive measures, with more affected patients having lower TSPO binding. The study by Hamelin and colleagues was the first to present results demonstrating that amyloid-positive control subjects (preclinical AD) had greater TSPO binding than amyloid-negative controls.…”
Section: Neuroinflammation In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation